Evaluation of Local Chicken Slaughter Operation, Carcas and Product Characteristics in Yogyakarta - Wahyu Supartono; Sri Raharjo; Sofyan Iskandar (Indonesian Association of Food Technologists, 2002)
Indonesian local chicken has some advantages in compared with broiler chicken. Local chicken can live freely and sometimes serves as